Understanding Markets with Socially Responsible Consumers - Kaufmann, Marc; Andre, Peter; Kőszegi, Botond (Quarterly Journal of Economics, 2024)
Abstract Many consumers care about climate change and other externalities associated with their purchases. We analyze the behavior and market effects of such “socially responsible consumers” in three parts. First, we develop a flexible theoretical framework to study competitive equilibria with rational consequentialist consumers. In violation of price taking, equilibrium feedback nontrivially dampens the impact of a person’s consumption on aggregate consumption, undermining the motive to mitigate. This leads to a new type of market failure, where even consumers who fully “internalize the externality” overconsume externality-generating goods. At the same time, socially responsible consumers change the relative effectiveness of taxes, caps, and other policies in lowering the externality. Second, since consumer beliefs about and preferences over their market impacts play a crucial role in our framework, we investigate them empirically via a tailored survey. Consistent with our model, consumers are often consequentialist, and many believe that they have a dampened impact on aggregate consumption. Inconsistent with our model, however, we also find many respondents who expect to have a one-to-one impact on aggregate consumption. Third, therefore, we analyze how such “naive” consumers modify our theoretical conclusions. They consume less than rational consumers in a single-good economy, but may consume more in a multigood economy with cross-market spillovers. A mix of naive and rational consumers may yield the worst outcomes.